Room‐temperature performance of 3 mm‐thick cadmium–zinc–telluride pixel detectors with sub‐millimetre pixelization. (17th August 2020) - Buttacavoli, Antonino; Principato, Fabio; Gerardi, Gaetano; Bettelli, Manuele; Sarzi Amadè, Nicola; Zappettini, Andrea; Seller, Paul; Veale, Matthew C.; Fox, Oliver; Sawhney, Kawal; Abbene, Leonardo
Abstract : In this work, the room‐temperature performance of 3 mm‐thick cadmium–zinc–telluride (CZT) pixel detectors with sub‐millimetre arrays is presented. The detectors allow high‐bias voltage operation (6000 V cm −1 electric field) with energy resolution values of less than 2 keV up to 140 keV. Abstract : Cadmium–zinc–telluride (CZT) pixel detectors represent a consolidated choice for the development of room‐temperature spectroscopic X‐ray imagers, finding important applications in medical imaging, often as detection modules of a variety of new SPECT and CT systems. Detectors with 3–5 mm thicknesses are able to efficiently detect X‐rays up to 140 keV giving reasonable room‐temperature energy resolution. In this work, the room‐temperature performance of 3 mm‐thick CZT pixel detectors, recently developed at IMEM/CNR of Parma (Italy), is presented. Sub‐millimetre detector arrays with pixel pitch less than 500 µm were fabricated. The detectors are characterized by good room‐temperature performance even at high bias voltage operation (6000 V cm −1 ), with energy resolutions (FWHM) of 3% (1.8 keV) and 1.6% (2 keV) at 59.5 keV and 122.1 keV, respectively. Charge‐sharing investigations were performed with both uncollimated and collimated synchrotron X‐ray beams with particular attention to recovering the charge losses at the inter‐pixel gap region. High rate measurements demonstrated the absence of high‐flux radiation‐induced polarization phenomena up to 25 × 10 6 photons mm −2 s −1 .